ALTAR SEBAGAI TEMPAT TERJADINYA PERISTIWA KESELAMATAN: TINJAUAN TEOLOGIS MENURUT ALFONSUS MARIA DE LIGUORI - Fransiskus Lado; Mateus Mali; Yohanes Subali (P3TK, Sanata Dharma University, 2022)
ABSTRACT:This article is a study to find the theological meaning of altar according to Saint Alphonsus Maria de Liguori. The author is interested in examining one of the peculiarities of Alphonsus' theology, namely the altar. The main focus of this writing is to find the theological meaning of the altar according to Alphonsus. The method used is a literature study. The main source of this research is the theological reflections generated from the writings of Alphonsus. The purpose of this article has two purposes. First, helping the Catholic people to experience the Eucharist more deeply when it is set with Alphonsus' understanding of the altar. Second, through this research, the readers can understand and take inspiration from the meaning of the altar in their daily lives.The theological meaning of the altar according to Alphonsus is the altar as an act of God's love, the altar as God's gift to humans, the altar as a symbol of the atoning sacrifice of Jesus Christ and the altar as a symbol of the unity of God and man.ABSTRAKArtikel ini merupakan kajian untuk menemukan makna teologis altar menurut Santo Alfonsus Maria de Liguori. Penulis tertarik untuk mengkaji salah satu kekhasan teologi Alfonsus, yaitu altar. Fokus utama tulisan ini adalah menemukan makna teologis altar menurut Alfonsus. Metode yang digunakan adalah studi kepustakaan. Sumber utama penelitian ini adalah refleksi teologis yang dihasilkan dari tulisan-tulisan Alfonsus. Artikel ini memiliki dua tujuan. Pertama, membantu umat Katolik untuk mengalami Ekaristi lebih mendalam ketika ditatapkan dengan pemahaman Alfonsus tentang altar. Kedua, melalui penelitian ini, pembaca dapat memahami dan mengambil inspirasi dari makna altar dalam kehidupan sehari-hari. Makna teologis altar menurut Alfonsus adalah altar sebagai tindakan cinta Allah, altar sebagai pemberian diri Allah kepada manusia, altar sebagai lambang kurban penebusan Yesus Kristus dan altar sebagai lambang kesatuan Allah dan manusia.